WASH and gender in health care facilities: The uncharted territory. Issue 1 (2nd January 2019) - Kohler, Petra; Renggli, Samuel; Lüthi, Christoph
ABSTRACT: Health care facilities in low- and middle-income countries are high-risk settings, and face special challenges to achieving sustainable water, sanitation, and hygiene (WASH) services. Our applied interdisciplinary research conducted in India and Uganda analyzed six dimensions of WASH services in selected health care facilities, including menstrual hygiene management. To be effective, WASH monitoring strategies in health care facilities must include gender sensitive measures. We present a novel strategy, showing that applied gender sensitive multitool assessments are highly productive in assessments of WASH services and facilities from user and provider perspectives. We discuss its potential for applications at scale and as an area of future research.